PEMBIAYAAN QARDH DENGAN MENGGUNAKAN DANA NASABAH - Feby Ayu Amalia (PROGRAM STUDI AKUNTANSI SYARIAH FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2020)
The development of Islamic finance in Indonesia has increased significantly, many akad-akad that has been applied to sharia banking. Islamic banks in their activities not only perform commercial activities that generate profits, but also Islamic banks are mandated to mensjahterkan ummah. Financing is one solution that can prosper the ummah, financing is taawun is financing by using qardh contract is the activity of channeling funds without any reward, but the customer must refund the funds. With the financing innovation by using qardh contract issued by Fatwa DSN-MUI Number: 79 / DSN-MUI / III / 2011 on qardh by using customer's fund, bank is given the flexibility to use customer's fund using qardh contract, for qardh is a product of demand deposits, savings or deposits using wadi'ah or mudharabah contracts. Qardh by using customer funds may be made as long as it does not deviate from the provisions of the fatwa and applicable Law, with the application of qardh funds Sharia Bank can slowly assist economic equity and economic prosperity.